Western Kentucky University - Harrison, Lowell H. (Lowell Hayes), 1922-2011 (Book collections on Project MUSE., 1987)
Most Hilltoppers believe that Western Kentucky University is unique. They take pride in its lovely campus, its friendly spirit, the loyalty of its alumni, and its academic and athletic achievements. But Western's development also illustrates a major trend in American higher education during the past century. Scores of other institutions have followed the Western pattern, growing from private normal school to state normal school, to teachers college, to general college, finally emerging as an important state university. Historian Lowell Harrison traces the Western story from the school's origin.